Wave Propagation over a Submerged Bar - L. H. Wiryanto (Institute for Research and Community Services (LPPM) ITB, 2010)
Based on small amplitude water theory we determine an exact solution for the amplitude of the reflected and transmitted waves produced when a monochromatic wave hits a submerged bar, a result of importance in coastal engineering. We compare the results obtained with results previously obtained in the long wave length limit and other numerical results. Using the results obtained we determine the optimal width or the bar of prescribed depth.